2003
DOI: 10.1590/s1517-74912003000200010
|View full text |Cite
|
Sign up to set email alerts
|

Candida spp. occurrence in oral cavities of breastfeeding infants and in their mothers' mouths and breasts

Abstract: AB STRACT:This study aimed to de ter mine the oc cur rence of Candida spp. in the oral cav ity of pre dom i nantly breast fed in fants and in their moth ers' mouths and breasts, as well as in the oral cav ity of bottlefed in fants and in non-lac tat ing women. One hun dred and sixty nine women and eighty-five milk-fed in fants took part in this study and were di vided into four groups: 1) in fants pre dom i nantly on breast feed ing (n = 55) and their moth ers (n = 55); 2) in fants on bottlefeeding (n = 30); 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 13 publications
5
22
2
4
Order By: Relevance
“…tropicalis (21,26). However, in contrast to other authors who reported C. glabrata to be the third most prevalent species after C. albicans and C. tropicalis, in the present study C.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…tropicalis (21,26). However, in contrast to other authors who reported C. glabrata to be the third most prevalent species after C. albicans and C. tropicalis, in the present study C.…”
Section: Resultscontrasting
confidence: 99%
“…C. glabrata was detected in only 1.7% of patients, a rate lower than the 7 to 24% reported by various studies (4,26).…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…The data indicated that C. albicans cells were more hydrophobic than C. parapsilosis cells. This could possibly explain why C. albicans is more frequently isolated from the oral cavity than non-Candida albicans species particularly, C. parapsilosis [6,19]. This may imply that nicotine has the ability to alter the surface characteristics of the microorganisms as demonstrated and, thus, increase the adsorption to the hydrocarbon hexadecane.…”
Section: Adherence Of C Albicans and C Parapsilosis Induced By The mentioning
confidence: 99%
“…It also points to the use of artificial nipples (from either a pacifier or a bottle) as a risk factor for Candida colonization. 9 Candida colonization of the lactating mother's breast is often asymptomatic, but overgrowth may cause it to become symptomatic. Symptoms can be anywhere along a continuum from red sore nipples that do not heal to debilitating breast pain.…”
Section: Generalmentioning
confidence: 99%